2022
DOI: 10.3389/fphar.2022.889142
|View full text |Cite
|
Sign up to set email alerts
|

The Ion Channel-Related Gene Signatures Correlated With Diagnosis, Prognosis, and Individualized Treatment in Patients With Clear Cell Renal Cell Carcinoma

Abstract: Background: Early detection and precise prognostic evaluation of clear cell renal cell carcinoma (ccRCC) are crucial for patient life expectancy. Ion channel-related genes (ICRGs) are of great diagnostic and prognostic value as components that maintain the normal structure of the kidney. Therefore, we systematically explored the diagnostic, prognostic, and therapeutic value of ICRGs in ccRCC using the multi-database.Methods: RNA transcriptome profiles and clinical data of ccRCC patients were extracted and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…11,12 Previous studies have also reported the use of SVM–REF screening for gene analysis of tumors. 13,14 In the present study, genes characteristic of pancreatic cancer screened by LASSO regression and SVM–REF were intersected to obtain the six pancreatic cancer signature genes SLPI , S100P , IFI27 , MSLN , DKK1 , and SERPINB5 . Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Previous studies have also reported the use of SVM–REF screening for gene analysis of tumors. 13,14 In the present study, genes characteristic of pancreatic cancer screened by LASSO regression and SVM–REF were intersected to obtain the six pancreatic cancer signature genes SLPI , S100P , IFI27 , MSLN , DKK1 , and SERPINB5 . Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Previous studies have also reported the use of SVM-REF screening for gene analysis of tumors. 13,14 In the present study, genes characteristic of pancreatic cancer screened by LASSO regression and SVM-REF were intersected to obtain the six pancreatic cancer signature genes SLPI, S100P, IFI27, MSLN, DKK1, and SERPINB5. Zhang et al 15 previously showed that SLPI is a multifunctional protein involved in regulating immune responses, inhibiting protease activity, and blocking the transcription of proinflammatory genes through the nuclear factor-kappa B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The comBat algorithm was then used to reduce the batch effects between the three datasets. We next screened and recorded 360 ion channel-related genes through an extensive literature review ( 24 26 ) and then intersected 330 genes downloaded from the HUGO Gene Nomenclature Committee (HGNC) database ( ), resulting in a total of 323 distinct ion channel-related genes. We analyzed these genes using univariate Cox regression to identify genes with prognostic significance for future studies.…”
Section: Methodsmentioning
confidence: 99%
“…↓ (Jiang et al, 2017) Clear cell renal cell carcinoma (ccRCC) ↓ (Zhu et al, 2022) Parathyroid carcinoma (PCA) ↑ (Adam et al, 2010) Prostate cancer (PCa) ↑ (Wu et al, 2020) Hepatocellular carcinoma (HCC) ↑ (Sun et al, 2022) Preterm birth (PTB) ↓ (Pereyra et al, 2019) Non-familial Brugada syndrome (BrS) KCNJ16 Ser261Gly (Juang et al, 2014) sudden infant death syndrome (SIDS) KCNJ16 R137S (Neubauer et al, 2022) The up arrow indicates the upregulation of KCNJ16 expression compared with the control group. The down arrow indicates the downregulation of KCNJ16 expression compared with the control group.…”
Section: Disease Expressionmentioning
confidence: 99%
“…Multiple ion channels are destroyed and altered during the development of ccRCC. Therefore, exploring the alteration of ion channels in the development of ccRCC may facilitate diagnosis and evaluation and inform the corresponding treatment (Zhu et al, 2022). Abnormally elevated KCNJ16 expression may also lead to carcinogenesis.…”
Section: Disease Expressionmentioning
confidence: 99%